Association between oral health and cardiovascular outcomes in patients with hypertension: a nationwide cohort study. Issue 2 (19th February 2022) - Kim, Jinkwon; Kim, Hyung Jun; Jeon, Jimin; Song, Tae-Jin
Abstract : Objective: Studies on the association of oral hygiene indicators with cardiovascular disease in hypertensive patients have been lacking. Oral hygiene is directly or indirectly associated with systemic inflammation, one of the essential mechanisms of cardiovascular disease. Therefore, we hypothesized that oral hygiene would be related to the risk of cardiovascular diseases in hypertensive patients. Methods: We included 52 677 hypertensive participants who completed oral health checkups from the Korean National Health Insurance Service-National Health Screening Cohort between 2003 and 2004. We collected data on periodontitis diagnosis and treatment history, number of teeth loss, number of dental caries, and frequency of tooth brushing from medical records of health claims and oral health examination. The primary outcome was defined as composite outcomes of stroke and myocardial infarction. Follow-up was done until the date of primary outcome, or 31 December 2015. Results: During the 11.26 ± 2.39 years (mean ± standard deviation) of the study follow-up, 3292 participants developed primary outcomes [stroke ( n  = 2430), myocardial infarction ( n  = 862)]. In multivariable Cox regression analyses, participants with dental caries (≥ 5) were independently associated with occurrence of a primary outcome [adjusted hazard ratio: 1.37; 95% confidence interval (CI):1.10–1.72; P  = 0.006]. Frequent tooth brushing (≥ 2 times/day) was significantly related to lower risk of primary outcomes (adjusted hazard ratio: 0.88; 95% CI: 0.81–0.96; P  = 0.002). Conclusion: Our study demonstrated that multiple dental caries were related to the risk of cardiovascular diseases in hypertensive patients. Better oral hygiene may attenuate the risk of cardiovascular events in hypertensive patients.